Reduction of the in vitro toxicity of elevated concentrations of SPIONLA by its administration through PHBV/curcumin composite microspheres - Aguilar-Rabiela, Arturo E.; Unterweger, Harald; Alexiou, Christoph; Boccaccini, Aldo R. (Frontiers in Biomaterials Science, 2022)
Superparamagnetic iron oxide nanoparticles have been developed for various biomedical applications for decades. In this work, lauric acid-coated SPION (SPIONLA) were incorporated into poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) at different ratios to produce composite microspheres, which were evaluated for their properties, including potential cytotoxicity. Additionally, a phytotherapeutic extract, curcumin, was loaded into the resulting microspheres to develop magnetic drug delivery capsules. The results show a significant improvement in the cytocompatibility after seven days of SPIONLA administrated in cells through the composite microspheres compared to pristine SPIONLA. The composite also exhibited prolonged cumulative release of curcumin in a simulated body fluid environment. The results confirmed the efficacy of the mixture of PHBV and curcumin in attenuating potential side effects due to direct administration of high initial amounts of SPIONLA while maintaining magnetic properties in the resulting composite. The results add evidence to the potential of these composite devices for targeted drug delivery applications.